Margret and H.A. Rey's Curious George makes pancakes - Rey, Margret; Rey, H. A. 1898- (Hans Augusto).; Vipah Interactive (Boston Houghton Mifflin, 1998)
Curious George, an inquisitive monkey, causes quite a stir when he tries his "hand" at making pancakes at a fundraiser for the children's hospital.
"Based on the character of Curious George, created by Margret and H.A. Rey"--T.p. verso.
Keywords: Monkeys -- Fiction; Pancakes, waffles, etc. -- Fiction; Fund raising -- Fiction